1993
DOI: 10.1177/019459989310800203
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome: A Review of 306 Consecutively Treated Surgical Patients

Abstract: Three hundred six consecutively treated surgical patients with obstructive sleep apnea syndrome were evaluated from a group of 415 patients. One hundred nine patients were excluded because they failed to obtain a postoperative polysomnogram or were lost to followup. All patients received a physical examination, cephalometric analysis, fiberoptic examination, and polysomnography before treatment to document OSAS and determine the areas of obstruction. A two-phase surgical protocol was used for the reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
402
2
32

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(452 citation statements)
references
References 20 publications
16
402
2
32
Order By: Relevance
“…When CPAP adherence is defi ned as > 4 hours of nightly use, 46% to 83% of OSA Several short term observational studies show that maxillomandibular advancement surgery (MMA) may be a clinically effective alternative therapy for patients with moderate-to-severe OSA who are not effectively treated with CPAP. [19][20][21][22][23][24][25][26] MMA involves surgical facial advancement by concomitant maxillary and mandibular osteotomies, thus enlarging the caliber of the posterior upper airway space. Although the level of evidence is low, substantial and consistent short-term reductions in the apnea-hypopnea index (AHI) are observed following MMA.…”
mentioning
confidence: 99%
“…When CPAP adherence is defi ned as > 4 hours of nightly use, 46% to 83% of OSA Several short term observational studies show that maxillomandibular advancement surgery (MMA) may be a clinically effective alternative therapy for patients with moderate-to-severe OSA who are not effectively treated with CPAP. [19][20][21][22][23][24][25][26] MMA involves surgical facial advancement by concomitant maxillary and mandibular osteotomies, thus enlarging the caliber of the posterior upper airway space. Although the level of evidence is low, substantial and consistent short-term reductions in the apnea-hypopnea index (AHI) are observed following MMA.…”
mentioning
confidence: 99%
“…Currently, the surgical treatment proposed tends to be a complementary procedure according to the case needs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, procedures that carry less severe risks and potential complications are performed initially. The Stanford group protocol reports a staged surgical success rate of 75 % in patients with mild-to-moderate OSA and 40 % in patients with severe OSA in phase I (palatal surgery alone or in combination with GA) to 95 % in phase II or facial skeletal surgery [53]. In some cases when soft tissue abnormalities are not considered to play a significant role, maxillomandibular advancement can be considered as the initial therapeutic option [45].…”
Section: Multi-level Surgery and Staged Surgerymentioning
confidence: 99%
“…Evidence has shown that single-site surgery has a poor success rate when multilevel obstruction is present. By combining surgical treatment modalities to address multiple levels of obstruction, the success rates can reach as high as 95 % in staged surgical protocols [53].…”
Section: Sleep Apnea Surgery In Childrenmentioning
confidence: 99%